2021
DOI: 10.1039/d1ra03981d
|View full text |Cite
|
Sign up to set email alerts
|

A new cross-conjugated mesomeric betaine

Abstract: Cross-conjugated mesomeric betaine (CCMB) has been defined as the dipolar species in which positive and negative charges are exclusively restricted to different parts of the molecule. A new CCMB isoconjugate with odd non-alternant hydrocarbon anion is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 60 publications
2
12
0
Order By: Relevance
“…The reaction of imidazo[1,2-a]pyridine with maleic anhydride proceeded almost similarly to its reaction with DMAD 12 , i.e., the reaction generates a 1,4-dipole (14) which subsequently reacts with a second molecule of maleic anhydride to form 15. Nevertheless, there are some distinct differences between the two reactions.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction of imidazo[1,2-a]pyridine with maleic anhydride proceeded almost similarly to its reaction with DMAD 12 , i.e., the reaction generates a 1,4-dipole (14) which subsequently reacts with a second molecule of maleic anhydride to form 15. Nevertheless, there are some distinct differences between the two reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Unambiguity of cyanosilylation of the betaine 57 allowed us to characterize the reaction product without isolation as 5-cyano-3-phenylamino-7-trifluoromethyl-1-trimethylsilyloxyindolizine 97 (Scheme 8). We rationalized the reaction mechanism, which includes O − −C5 addition of TMSCN, followed by [1,9]H-shift. The addition starts from the nucleophilic attack of the cyanide ion, since no reaction was observed when we changed TMSCN to TMSCl in the same reaction conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It was found that their C3 position undergoes a thermodynamically controlled intramolecular nucleophilic attack, while the C5 position is prone to reversible addition of O-and S-nucleophiles. With TMSCN as a C-nucleophile, subsequent silylation of exocyclic oxygen at C1 occurs, giving 5-cyano-3-phenylamino-1-trimethylsilyloxyindolizine after [1,9]H-shift. Hydroperoxide-promoted oxygenation at the C5 position affords novel 1,5-dioxo-3-arylamino-1,5-dihydroindolizines.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 2 more Smart Citations